Roles of the rpoEc-chrR-chrA operon in superoxide tolerance and β-lactam susceptibility of Stenotrophomonas maltophilia - Ku, Ren-Hsuan; Lu, Hsu-Feng; Li, Li-Hua; Yeh, Ting-Yu; Lin, Yi-Tsung; Yang, Tsuey-Ching (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe rpoE-chrR pair is a regulatory system used by photosynthetic microorganisms to overcome singlet oxygen stress. rpoE and chrR encode the sigma factor σE and anti-sigma factor ChrR, respectively. Stenotrophomonas maltophilia, an opportunistic pathogen, is a multidrug-resistant gram-negative bacterium. Although it is not a photosynthetic microorganism, a rpoE-chrR homolog (smlt2377-smlt2378) was found in the S. maltophilia genome. In this study, we aimed to assess the significance of σEc-ChrR pair in oxidative stress alleviation and antibiotic susceptibility of S. maltophilia KJ.MethodsReverse transcription-polymerase chain reaction was used to validate the presence of operon. The contribution of rpoEc-chrR-chrA operon to oxidative stress alleviation and antibiotic susceptibility was evaluated using mutant constructs and stress-tolerance assays. RNA-seq transcriptome assay of wild-type KJ, KJΔChrR (chrR mutant), and KJΔChrRΔRpoEc (chrR/rpoEc double mutant) was performed to reveal the σEc regulon.ResultsThe rpoEc-chrR pair and downstream chrA formed an operon. Inactivation of chrR upregulated the expression of rpoEc-chrR-chrA operon in an σEc- and ChrA-dependent manner. σEc activation contributed to superoxide tolerance and increased β-lactam susceptibility but did not affect the tolerance to singlet oxygen and hydrogen peroxide. Transcriptome analysis revealed that expression of the nine-gene cluster, smlt2375-smlt2367, was significantly upregulated in KJΔChrR and reverted to the wild-type level in KJΔChrRΔRpoEc. smlt2375-smlt2367 cluster was located upstream of the rpoEc-chrR-chrA operon and divergently transcribed, seeming to be involved in membrane lipid modification. Deletion of smlt2375-smlt2367 cluster from the chromosome of KJΔChrR reverted the superoxide tolerance and β-lactam susceptibility to the wild-type level.DiscussionThe rpoEc-chrR pair of S. maltophilia was involved in superoxide tolerance and β-lactam susceptibility. Notably, a novel regulatory circuit involving rpoEc-chrR-chrA operon and smlt2375-smlt2367 cluster was revealed.